2010
DOI: 10.1016/j.ajog.2010.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel multiple marker assay vs the Risk of Malignancy Index for the prediction of epithelial ovarian cancer in patients with a pelvic mass

Abstract: Objectives To compare the Risk of Malignancy Index (RMI) to the Risk of Ovarian Malignancy Algorithm (ROMA) to predict EOC in women with a pelvic mass. Study Design 457 women with imaging results from ultrasound, CT and MRI, and serum HE4 and CA 125 determined prior to surgery for pelvic mass were evaluable. RMI values were determined using CA 125, imaging score and menopausal status. ROMA values were determined using HE4, CA 125, and menopausal status. Results At a set specificity of 75%, ROMA had a sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
3
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(240 citation statements)
references
References 20 publications
12
217
3
8
Order By: Relevance
“…Our results are somewhat consistent with those of previous studies (Hellström et al, 2003;Moore et al, 2008;Huhtinen et al, 2009;Montagnana et al, 2009;Moore et al, 2009;Moore et al, 2010;Nolen et al, 2010;Bandiera et al, 2011;Molina et al, 2011;Park et al, 2011;Van Gorp et al, 2011;Karlsen et al, 2012;Park et al, 2012), which reported that serum CA125 and HE4 levels were significantly higher in ovarian cancer women than those in benign ovarian tumor women and in healthy women. In accordance with previous observations , our results showed that serum CA125 and HE4 levels were found to be related to FIGO stage with higher concentrations in late stages (stage III/IV) than in early stages (stage I/II).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are somewhat consistent with those of previous studies (Hellström et al, 2003;Moore et al, 2008;Huhtinen et al, 2009;Montagnana et al, 2009;Moore et al, 2009;Moore et al, 2010;Nolen et al, 2010;Bandiera et al, 2011;Molina et al, 2011;Park et al, 2011;Van Gorp et al, 2011;Karlsen et al, 2012;Park et al, 2012), which reported that serum CA125 and HE4 levels were significantly higher in ovarian cancer women than those in benign ovarian tumor women and in healthy women. In accordance with previous observations , our results showed that serum CA125 and HE4 levels were found to be related to FIGO stage with higher concentrations in late stages (stage III/IV) than in early stages (stage I/II).…”
Section: Discussionsupporting
confidence: 93%
“…There may be several explanations for the heterogeneity observed among previous studies, and in our opinion, the most intriguing are the differences in the study design, study population, demographic characteristics of patients, ovarian cancer prevalence, sample size, control group (healthy women or women with benign diseases), methods of measuring serum CA125 or HE4 levels (ELISA or chemiluminescent microparticle immunoassay) and cutoff values of CA125/HE4 assays (manufacturer or clinical practice). Furthermore, several studies did not take into account the effect of the uneven distribution of patients in pre-and post-menopausal status, histological subtypes and FIGO stages when interpreting the results of CA125 and HE4 measurements (Moore et al, 2009;Moore et al, 2010;Kim et al, 2011;Montagnana et al, 2011;Ruggeri et al, 2011;Van Gorp et al, 2011). Overall, each of these points theoretically represent a source of heterogeneity among studies likely influencing the markers' diagnostic performances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The advantage of HE4 over CA125 is mainly in the detection of borderline ovarian tumors and early-stage epithelial ovarian and tubal cancers. 4 A normal HE4 value in this situation would imply the differential diagnosis of a benign endometrioma rather than ovarian cancer, and this patient could therefore be operated on laparoscopically by a gynecologist. Both markers showed similar diagnostic performance in the detection of epithelial ovarian cancer at clinically defined thresholds (CA125 35 U/mL; HE4 70 pM), but HE4 was not elevated in endometriosis.…”
Section: Diagnosismentioning
confidence: 96%
“…The war taking five years increases the child deaths under age of 5 by 13%. Also 47% of all the refugees in the world and 50% of asylum seekers and displaced people are women and girls and 44% refugees and asylum seekers are children under the age of 18 (5). As the result of wars and armed conflicts, women are…”
Section: Mortalities and Morbiditiesmentioning
confidence: 99%